NEXIALISM AS AN EMERGING INTERDISCIPLINARY CONSTRUCT: A SYSTEMATIC LITERATURE REVIEW AND PROPOSAL FOR AN OPERATIONAL CONCEPTUAL MODEL - Martins, Frederico Cordeiro (Seven Editora, 2026)
The increasing complexity of contemporary problems has revealed structural limitations of disciplinary hyper-specialization, particularly in sociotechnical, regulatory, and educational contexts. In this scenario, the concept of nexialism, originally derived from science fiction, has been sporadically appropriated by academic literature as a metaphor and heuristic for knowledge integration. This article aims to systematically map the scientific literature that employs the terms nexialism and nexialist, critically analyze their conceptual uses, and propose a theoretical-operational model that enables empirical application. A qualitative systematic literature review was conducted following PRISMA-inspired guidelines, using recognized scientific databases. Results indicate that nexialism does not constitute a consolidated theoretical field but emerges as an interdisciplinary construct associated with knowledge integration, mediation among specialists, systems thinking, and the management of unintended consequences. Based on thematic synthesis, a conceptual model with five latent dimensions and an initial measurement framework is proposed. The study concludes that nexialism holds significant analytical potential for addressing complex problems, although systematic empirical validation remains necessary.DOI: https://doi.org/10.56238/sevened2026.008-057